Encyclopedia of Polymer Science and Technology 2001
DOI: 10.1002/0471440264.pst256
|View full text |Cite
|
Sign up to set email alerts
|

Polycyanoacrylates

Abstract: Cyanoacrylates are important materials in the production of rapidly curing structural adhesives. The monomers are generally low viscosity liquids, which are prepared in a two‐step process by a base‐catalyzed condensation of paraformaldehyde and cyanoacetate, followed by thermally induced depolymerization of the resultant oligomer under acidic conditions. The monomers are highly reactive toward basic materials and undergo extremely rapid anionic polymerization on contact with catalytic amounts of even weakly nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Alkyl 2-cyanoacrylates or cyanoacrylates (CAs) are a family of vinyl monomers renowned for their high reactivity, instant adhesive properties, and wide-ranging applications [1,2,3,4,5,6]. Short chain CAs, like methyl- and ethyl 2-cyanoacrylate have found great utility as the major components of industrial and household instant adhesives or “super glues”, including those manufactured at Henkel under the Loctite brand (Table 1) [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alkyl 2-cyanoacrylates or cyanoacrylates (CAs) are a family of vinyl monomers renowned for their high reactivity, instant adhesive properties, and wide-ranging applications [1,2,3,4,5,6]. Short chain CAs, like methyl- and ethyl 2-cyanoacrylate have found great utility as the major components of industrial and household instant adhesives or “super glues”, including those manufactured at Henkel under the Loctite brand (Table 1) [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Short chain CAs, like methyl- and ethyl 2-cyanoacrylate have found great utility as the major components of industrial and household instant adhesives or “super glues”, including those manufactured at Henkel under the Loctite brand (Table 1) [4,5,6]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excellent adhesive properties of polycyanoacrylates (PCA) have enabled their widespread use for many household applications (Super Glue®), and, most recently for applications in medicine,12 surgery,13 ophthalmology,14 dentistry,15 tissue reconstruction,16 and for drug delivery,17 due to their biocompatibility and biodegradability. Various other applications for CAs include fingerprint detection for forensic applications, coating for lithographic printing plates, waveguides for optical sensors, photoresists and holographic recording media, which exploit their rapid polymerizability or the optical properties of their polymers 18. However their use as designer materials is scarce partly due to the difficulty of controlling their polymerization and copolymerization processes.…”
mentioning
confidence: 99%
“…Kotzev et al (1981 showed that at 150°C a total loss of ethyl-2-cyanoacrylate adhesive properties occurred ( (Kotzev et al, 1981), p1946). Woods (2001), (p647) documents that the poly-cyanoacrylate group of polymers "undergo retro-polymerisation reactions at temperatures in the vicinity of 140°C to 180°C".…”
Section: 2514mentioning
confidence: 99%